Cellular immune function monitoring after allogeneic haematopoietic cell transplantation: evaluation of a new assay. (18th April 2013) - Israeli, M.; Klein, T.; Herscovici, C.; Ram, R.; Shpilberg, O.; Sredni, B.; Yeshurun, M.
Summary Managing the patient's immune system after haematopoietic cell transplantation (HCT) is a challenge, mainly in the unstable period immediately after the transplant. Currently there is no standardized non‐invasive diagnostic tool for the evaluation of immunological complications such as graft‐versus‐host disease (GVHD) and for managing the cellular immune function of the transplant recipient. The ImmuKnow assay for cellular immune function monitoring has been incorporated successfully into the clinical follow‐up routine of solid organ transplant recipients. This study aims to explore the relevance and potential contribution of immune monitoring using the assay in the setting of HCT. We found that ImmuKnow‐level measurement can distinguish between states of immune function quiescence and between events of acute GVHD. ImmuKnow levels were significantly higher in patients going through GVHD than the levels measured for the same patients during immunological stability. Moreover, we demonstrate a patient case where longitudinal monitoring using the ImmuKnow assay provided a trustworthy depiction of the patient's cellular immune function post‐HCT. In conclusion, we provide evidence for the potential contribution of the ImmuKnow assay for longitudinal individualized cellular immune function monitoring of patients following HCT. Further studies are necessary in order to establish the optimal practice for utilizing the assay for this purpose.